Inducible mouse model of skeletal muscle specific deletion of the Vitamin D Receptor (VDR) - Centeno, Viviana Andrea (2022)
Fil: Centeno, Viviana Andrea. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra Química Biológica A; Argentina.